Non-Adherence in Adult Male Patients with Community-Acquired Pneumonia: Relative Forgiveness of Amoxicillin versus Respiratory Fluoroquinolones - Nerea Carral; John C. Lukas; Oskar Estradé; Nerea Jauregizar; Héctor Morillas; Elena Suárez (MDPI AG, 2023)
The consequences of non-adherence to treatment (NAT) on antimicrobial efficacy may depend on drug forgiveness-a property that should account for pharmacokinetics (PK) and pharmacodynamics (PD) as well as interindividual variability. In this simulation study, relative forgiveness (RF) in NAT, defined as the probability of a successful PK/PD target (PTA) attained under perfect adherence compared to imperfect adherence, was evaluated for amoxicillin (AMOX) (oral 1000 mg/8 h) and two respiratory fluoroquinolones-levofloxacin (LFX) (oral 750 mg/24 h) and moxifloxacin (MOX) (oral 400 mg/24 h)-in virtual outpatients with community-acquired pneumonia for S. pneumoniae. Several NAT scenarios (delay in dose intake and a missed dose) were considered. PK characteristics of virtual patients, including variability in creatinine clearance (70-131 mL/min) and S. pneumoniae susceptibility variability associated with geographical location, were simulated in NAT. In this regard, in regions of low MIC delays from 1 h to 7 h or omission of dose ingestion would not have negative consequences on the efficacy of AMOX because of its good RF associated with the AMOX PK and PD properties; RF of LFX 750 mg or MOX 400 mg/24 h regimen vs. AMOX 1000 mg/8 h is one. However, in regions of elevated MIC for S. pneumoniae AMOX loses its RF, LFX and MOX vs. AMOX, showing higher RF (>1) depending on the CLCR of patients. These results illustrate the importance of considering the RF of antimicrobial drugs in NAT and provide a framework for further studying its implications for clinical success rates.